Comparative Effectiveness of Letrozole versus Metformin for Ovulation Induction in Women with PCOS - I Komang Tri Yasa Widnyana; Aditya Prabawa; Putu Ayu Sintya Dewi (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: This study serves to compare the effectiveness of letrozole and metformin for ovulation induction in women with polycystic ovary syndrome based on ovulation, pregnancy, and live birth outcomes.Methods: This study was conducted as a systematic review and meta-analysis following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Literature searches were performed in PubMed, Scopus, Web of Science, the Cochrane Library, and ScienceDirect. Randomized controlled trials comparing letrozole and metformin in women with polycystic ovary syndrome were included. Primary outcomes included ovulation rate, clinical pregnancy rate, and live birth rate.Result: Fourteen randomized controlled trials involving 3,314 patients were analyzed. Meta-analysis showed that letrozole significantly improved ovulation rate compared to metformin (odds ratio 1.29; 95% confidence interval 1.09-1.53). Letrozole also demonstrated superior clinical pregnancy outcomes (odds ratio 1.65; 95% confidence interval 1.41-1.93) and higher live birth rates (odds ratio 1.49; 95% confidence interval 1.26-1.75). Metformin primarily improved metabolic parameters but showed limited effectiveness as monotherapy for reproductive outcomes.Discussion: Letrozole acts directly on ovarian follicular development, whereas metformin mainly improves insulin resistance. These differences explain the superior reproductive outcomes observed for letrozole.Conclusion: Letrozole is more effective than metformin for ovulation induction and reproductive outcomes in women with polycystic ovary syndrome and should be considered a first-line therapy.Perbandingan Efektivitas Letrozole versus Metformin untuk Induksi Ovulasi pada Wanita dengan PCOSAbstrakTujuan: Penelitian ini bertujuan untuk membandingkan efektivitas letrozol dan metformin dalam induksi ovulasi pada wanita dengan sindrom ovarium polikistik berdasarkan luaran ovulasi, kehamilan, dan kelahiran hidup.Metode: Penelitian ini merupakan tinjauan sistematis dan meta-analisis yang mengikuti pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Pencarian literatur dilakukan pada basis data PubMed, Scopus, Web of Science, Cochrane Library, dan ScienceDirect. Uji klinis teracak yang membandingkan letrozol dan metformin pada pasien sindrom ovarium polikistik dimasukkan dalam analisis. Luaran utama meliputi angka ovulasi, angka kehamilan klinis, dan angka kelahiran hidup.Hasil: Sebanyak 14 uji klinis teracak dengan total 3.314 pasien dianalisis. Meta-analisis menunjukkan bahwa letrozol secara signifikan meningkatkan angka ovulasi dibandingkan metformin (rasio odds 1,29; interval kepercayaan 95% 1,09 - 1,53). Letrozol juga menunjukkan angka kehamilan klinis yang lebih tinggi (rasio odds 1,65; interval kepercayaan 95% 1,41 - 1,93) serta peningkatan angka kelahiran hidup (rasio odds 1,49; interval kepercayaan 95% 1,26 - 1,75). Metformin terutama memperbaiki parameter metabolik hanya saja memiliki efektivitas yang lebih terbatas terhadap luaran reproduksi jika digunakan sebagai monoterapi.Diskusi: Letrozol bekerja langsung pada perkembangan folikel ovarium, sedangkan metformin terutama memperbaiki resistensi insulin. Perbedaan mekanisme ini menjelaskan keunggulan luaran reproduksi pada terapi letrozol.Kesimpulan: Letrozol lebih efektif dibandingkan metformin dalam induksi ovulasi dan luaran reproduksi pada wanita dengan sindrom ovarium polikistik.